Lumpy Skin Disease: An Emerging Threat to Livestock in Tehsil Bara, Pakistan: Lumpy skin disease a threat to livestock - Azam Jan Afridi; Amina Zuberi; Ali Muhammad Yousafzai; Syed Ahsan Shahid; Muhammad Kamran; Sonaina Kanwal (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Lumpy skin disease (LSD) is a highly contagious and significant economic disease of cattle caused by a virus belonging to the family Poxviridae and genus Capripoxvirus. The present study aimed to determine the severity of the lumpy skin disease outbreak and associated losses in tehsil Bara, Pakistan. The data was collected through a questionnaire from farmers who have cows in their homes; the reported data varied in five different areas of tehsil Bara, collected from June 1, 2022, to August 31, 2022. The total number of reported cases from five selected areas were 2021, of which 168 were healthy and 1853 were infected. Out of the total infected 766 were recovered and 922 were in the recovery stage. Out of five selected areas, the disease’s highest infection followed by the highest mortality rate and lowest recovery cases were 466 (96.28 %), 59 (12.66 %), and 173 (37.12 %) respectively, recorded from Shlobar Quam. The lowest mortality rate was 8 (4.65 %) recorded from Nala Sourdandh and the highest recovery rate was 113 (53.30 %) recorded from Bar Qambar Khel. The disease is characterized by widespread nodules on the skin and causes decreased milk production and lack of appetite, and animals show pharyngeal and nasal secretions, accompanied by secondary infection. It is transmitted by the transportation of illegally bought and sold animals across borders to a new area and spread by insect vectors, including biting flies, mosquitoes, and ticks. Antibiotics, antihistamines, analgesicantipyretics, immunity boosters, and the management of wounds are the general lines of treatment. The current study recommends the multi-task role of government, and the private sector, as well as the isolation of infected animals, burial of dead bodies, annual vaccination, and the prevention of illegal transportation across the border.